Caregiving in rural areas: A qualitative study of challenges and resilience - Hyojin Choi; Christine Vatovec; Maija Reblin (PLoS ONE, 2025)
Background and objectives Informal caregivers are critical to providing support to adults with functional limitations or disease in rural areas. There is a need to understand factors that impact rural caregiving to build equitable health services, yet there is a lack of research that weighs both strengths and challenges. Our goal is to examine these factors as identified by rural caregivers in qualitative interviews. Research design and methods A purposive sample of rural-dwelling caregivers (n = 18) was recruited from a state-wide registry in a predominantly rural state. Semi-structured interviews were conducted by phone and interview transcripts were qualitatively analyzed. Results We identified areas of strengths and resilience among rural caregivers, including informal support from friends and neighbors, which often bridged gaps in formal services. Rural caregivers also identified barriers to service use, such as long distance, travel and a lack of awareness within the healthcare system. Discussion and implications These challenges increase caregivers’ needs for tailored family centered care coordination and highlight the necessity of providing diverse care delivery options. Our findings highlight that community-based efforts and policy should address barriers and rural disadvantage, while also fostering and empowering the resilience of caregivers in their rural home environment.